(untitled) (Palíndromo, 2026)
This article examines the work of the Comunidad Catrileo+Carrión, a non-binary Mapuche collective from Chile that mobilizes artistic and political practices related to weaving, performance, and dissident ancestry. The aim is to understand how the concept of epupillan — a free spiritual being that does not conform to cisheteronormative frameworks — guides processes of historical reinscription and the reactivation of memories silenced by coloniality and the heteropatriarchal regime. The methodology combines performative writing, critical analysis of visual and corporeal materials, and speculative procedures that articulate fabulation and the evocation of memories, understanding creation as a situated practice. The results indicate that photography, the body, archives, and the land operate as narrative dispute devices and as technologies of collective care, enabling the affirmation of dissident existences. The conclusion suggests that writing, thought alongside weaving, constitutes an act of resistance and world-making, proposing ways of living and remembering grounded in alliances between human and non-human beings, non-linear temporalities, and insurgent affects.